Analisis Faktor-Faktor yang Memengaruhi Tingkat Kepatuhan Wajib Pajak Orang Pribadi di Lingkungan Kantor Pelayanan Pajak Pratama, Tigaraksa Tangerang - Maya Tantio Dharma; Stefanus Ariyanto (Binus Business Review, 2014)
Tax collection is not an easy matter. Active participation from the tax authorities also requires the willingness of the taxpayer. A public reaction can be seen from the taxpayer’s willingness to pay taxes. Willingness and awareness to pay taxes represent a value contributed by someone (which has been determined by regulation). Tax is used to finance public expenditures without any direct benefit. Taxpayer’s awareness about taxation functions as state funding is needed to improve tax compliance and to determine the level of tax compliance in implementing their tax obligations. Limitation of the scope of this study is the effect of the level of awareness of paying taxes, taxpayer’s understanding about tax benefits, tax penalties, and understanding of service quality to the tax authorities of individual taxpayer compliance in the fulfillment of tax obligations, as well as restricted to data obtained through questionnaires received and filled by the individual taxpayer of Tigaraksa Pratama Tax Office area. Data were obtained through questionnaire and processed and analyzed using parametric statistical tests and multiple linear regression with 4 independent variables and one dependent variable resulted in the conclusion that the factors that most influence taxpayer compliance in carrying out its tax liability is the use of sanctions against taxpayers who do not carry out its obligations under applicable legislation.